Enhanced Diagnostic Accuracy of Fast-Field Echo Resembling a Computed Tomography Using Restricted Echo-Spacing for Hand Tendon Injuries: A Comparative Study - Yukari Matsuzawa, MD, PhD; Yusuke Matsuura, MD, PhD; Kaoru Kitsukawa, MD, PhD; Takahiro Yamazaki, MD, PhD; Kayo Inaguma, MD; Seiji Ohtori, MD, PhD (Journal of Hand Surgery Global Online, 2025)
Purpose: Fast-field echo resembling a computed tomography using restricted echo-spacing (FRACTURE), a magnetic resonance imaging (MRI) sequence (Philips Healthcare) providing computed tomography-like bone contrast, enables excellent visualization of bones and tendons. Volume rendering (VR) images created from this sequence show anatomical details of a patient’s actual structures. This study evaluated the diagnostic performance of FRACTURE and its VR images for visualizing wrist tendons on MRI images from patients and healthy individuals. Methods: Twenty subjects were included, 10 patients with tendon injuries and 10 healthy individuals who underwent MRI scanning. The imaging protocols were FRACTURE (with VR images), T2-weighted imaging (T2WI), and proton density-weighted volumetric isotropic turbo-spin-echo acquisition (PD-VISTA). An orthopedic surgeon, a hand-surgery specialist, and a radiologist not involved in the surgeries used three methods to interpret the images: FRACTURE multiplanar reconstruction, FRACTURE VR, and PD-VISTA + T2WI. The assessment criteria included tendon injury diagnostic accuracy, interpretation time, and ease-of-interpretation scoring. Diagnostic accuracy was calculated as the correct diagnosis rate. Interpretation time and scoring were analyzed by paired t tests and Bonferroni correction for multiple comparisons. Results: Fast-field echo resembling a computed tomography using restricted echo-spacing VR showed the highest tendon injury diagnostic accuracy, with considerably better interpretation time performance and ease-of-interpretation scoring versus PD-VISTA + T2WI. In the surgical cases, the tendon rupture sites on FRACTURE images corresponded to the intraoperative findings. Conclusions: Fast-field echo resembling a computed tomography using restricted echo-spacing was excellent across all assessment criteria, and FRACTURE VR had particularly high diagnostic performance and clinical utility. Although obliquely oriented tendons, such as of the thumb and little finger, require consideration of the magic angle effect, clear visualization of these tendons was possible with appropriate positioning. Additionally, FRACTURE’s high tendon visualization capability enabled the identification of anatomical variations, enhancing its usefulness in clinical hand-surgery practice. Clinical relevance: Tendon injury diagnosis was faster and more accurate with FRACTURE VR than with conventional sequences.